Determinants of the number of impoverished people in Central Java, Indonesia - Ananda Rafif Irsyad Nugroho; Muhammad Arif (Journal of Enterprise and Development (JED), 2024)
Purpose — This research aims to estimate the impact of the education index, health index, poverty alleviation budget, and purchasing power on the number of impoverished people.Method — This study employs panel data regression, utilizing samples from 35 regencies/cities in Central Java Province with annual data spanning from 2016 to 2022. The data is processed using Eviews 10 software.Result — By using the Fixed Effects Model (FEM) approach, we found that the education index and health index have a positive impact on reducing the number of impoverished people, while the poverty alleviation budget and purchasing power have a negative impact on the number of impoverished people.Novelty  — This research adds value by focusing on purchasing power and poverty alleviation budgets, which have been less explored in previous studies. By delving into these aspects, the research provides a deeper understanding of the poverty dynamics in Central Java Province, offering new insights and more targeted solutions to effectively address poverty-related issues.